2022
DOI: 10.3390/cancers14205070
|View full text |Cite
|
Sign up to set email alerts
|

Understanding Mechanisms of RKIP Regulation to Improve the Development of New Diagnostic Tools

Abstract: One of the most dangerous aspects of cancer cell biology is their ability to grow, spread and form metastases in the main vital organs. The identification of dysregulated markers that drive intracellular signalling involved in the malignant transformation of neoplastic cells and the understanding of the mechanisms that regulate these processes is undoubtedly a key objective for the development of new and more targeted therapies. RAF-kinase inhibitor protein (RKIP) is an endogenous tumour suppressor protein tha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

1
6
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
3
2

Relationship

0
5

Authors

Journals

citations
Cited by 8 publications
(7 citation statements)
references
References 75 publications
1
6
0
Order By: Relevance
“…In fact, in most of the studies published so far, significant reduction in RKIP levels has been described, correlated proportionally with the aggressiveness and ability of tumors to form metastases. Thus, there is a close association between reduced RKIP expression and the progression of various cancers including NSCLC [18]. However, most of the cited studies mainly focused on the expression RKIP in tumour tissues, while there is little evidence on blood expression of RKIP and pRKIP.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…In fact, in most of the studies published so far, significant reduction in RKIP levels has been described, correlated proportionally with the aggressiveness and ability of tumors to form metastases. Thus, there is a close association between reduced RKIP expression and the progression of various cancers including NSCLC [18]. However, most of the cited studies mainly focused on the expression RKIP in tumour tissues, while there is little evidence on blood expression of RKIP and pRKIP.…”
Section: Discussionmentioning
confidence: 99%
“…In this context, there is a growing interest for Raf Kinase Inhibitor Protein (RKIP), an endogenous inhibitor of Raf Kinase, widely expressed in human tissues. RKIP function is finely regulated at translational [13] and post-translational levels by microRNAs [14,15] and post translational modifications such phosphorylation [16,17] that inhibit its function and, in turn, activate the Raf kinase pathway, a key regulator of many cellular functions, such as proliferation, differentiation, survival, and angiogenesis often involved in the progression of many neoplasms [18]. A number of independent studies have shown that RKIP is frequently downregulated in many types of neoplasms, including non-small cell lung cancer (NSCLC) [19], and its downregulation is often associated with an increase in invasiveness and the ability to form metastases [20] which, overall, contributes to a greater severity [21] and worse overall survival, especially in advanced-stage NSCLC [22].…”
mentioning
confidence: 99%
“…However, the deletion events happen in only a minority of samples. By contrast, several transcription factors and small RNAs were found to target RKIP in cancer cells selectively ( 45 ). We proposed MTDH as a novel factor that controls the RKIP transcription, which is essential for cancer progression ( 46 ).…”
Section: Discussionmentioning
confidence: 99%
“…On the other hand, downregulation or loss of RKIP expression has regularly been observed in many cancers, a fact that is mainly attributed to the altered epigenetic landscape (e.g., promoter methylation and epigenetic transcription silencing) rather than RKIP allele deletion or mutational events [54,55]. Although a pan-cancer computational analysis of RKIP expression and relevant associations with clinicopathological features including disease progression, metastasis, and therapeutic response are still missing from the literature, a general picture from individualized cancer types reveals that RKIP expression can be used as an independent prognostic marker for overall survival and disease-free survival [2,56]. Notably, the prognostic value of phosphorylated at Ser 153 RKIP protein levels (pSer153 RKIP), known to weaken its tumor suppressing activity, is still limited, as it has been studied in only a few cancer types [57][58][59][60][61].…”
Section: Discussionmentioning
confidence: 99%